Worst case scenario match analysis and contextual variables in professional soccer players: a longitudinal study - Oliva-Lozano, José M.; Rojas-Valverde, Daniel; Gómez-Carmona, Carlos D.; Fortes, Víctor; Pino-Ortega, José (Biology of Sport, 2020)
This study aimed to describe the worst-case scenarios (WCS) of professional soccer players by playing position in different durations and analyse WCS considering different contextual variables (match half, match location and match outcome). A longitudinal study was conducted in a professional soccer team. Data were collected from different WCS durations in the total distance (TD), high-speed running distance (HSRD), and sprinting distance (SPD). A mixed analysis of variance was performed to compare different WCS durations between playing positions and contextual variables, making pairwise comparisons by Bonferroni post hoc test. Positional differences were found for TD (p < 0.01, ωp 2 = 0.02), HSRD (p < 0.01, ωp 2 = 0.01) and SPD (p < 0.01, ωp 2 = 0.02). There was a significant interaction when comparing WCS by match half in TD (F = 6.1, p < 0.01, ωp 2 = 0.07) but no significant differences in HSRD (p = 0.403, ωp 2 = 0) or SPD (p = 0.376, ωp 2 = 0). A significant interaction was identified when comparing WCS by match location in TD (F = 51.5, p < 0.01, ωp 2 = 0.14), HSRD (F = 19.15, p < 0.01, ωp 2 = 0.05) and SPD (F = 8.95, p < 0.01, ωp 2 = 0.01) as well as WCS by match outcome in TD (F = 36.4, p < 0.01, ωp 2 = 0.08), HSRD (F = 13.6, p < 0.01, ωp 2 = 0.04) and SPD (F = 7.4, p < 0.01, ωp 2 = 0.02). Positional differences exist in TD, HSRD, and SPD in match-play WCS, and contextual variablessuch as match half, match location and match outcome have a significant impact on the WCS of professional soccer players.